(3GdLhGgQ GdMSGf aj JMbjb eYQaI CQcGf GdEjeGfs ((3fYeI Hf CMeO Hf eMeO Hf MejOg s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO , GdaQO GdUeO hHYO aGYde Cf CSYO GdYHGO ef Mbb eYQaI eG ChLH Gddg Ydjg ef eSGFd GdEYJbGO ESJNQJ Gddg ai LeY YbjOI CSJhai ajgG LejY eG jTJQW ai GdEjeGf ef CQcGfg GdeYJHQg s
(3BNQgG (B:s
(3EYde Cf GdEjeGf HGdbOQ Ydi bSejf (B: (3CMOgeG (B: (3GdEjeGf HCfg SHb ai Ydeg eG faYdg ef NjQ hTQ hKGfjgeG Cfg (B_ (3JYGdi (B_ (3Ndb GaYGd GdYHGO cdgG ef TQ hNjQ hcaQ hEjeGf hbO GfJgi eGQeJg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV YHGQJgG HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJhMjO hGdedd hGdfMds